Pengaruh Faktor-Faktor Motivasi Terhadap Produktivitas Kerja Karyawan Pada Rumah Sakit Pertamina Bintang Amin Bandar Lampung - Sri Murtini; Agus Sutardjo; Bambang Purwanto (Universitas Malahayati, 2013)
Human resources is still very important and be the center of attention in an organization orcompany to survive in the era of globalization coupled with increasing competition levels.Productivity is closely linked to the progress and success of a company. The company will not besuccessful if not supported by the productivity of its employees. Employee productivity increaseswhen employees are motivated to work. Motivation can be defined as an individual's personalcircumstances that encourage the desire of individuals to perform certain activities in order to achievea goal. In this research the Influence Factors of Motivation Of Employee Productivity At Rumah SakitPertamina Bintang Amin were discussed.Data collection methods used in this research was by usingquestionnaires or questionnaire with a sample of all employees remains at Rumah Sakit PertaminaBintang Amin totaling 47 respondents comprising of the employees at the Medical Inpatient,Outpatient and Midwives whereas analytical models used was a multiple linear regression wereprocessed using SPSS 16 software. The results of this study stated that motivational factors with RSquare of 0.473 or 47.3% and the remaining 52.7% (100% -47.3%) affected by other factors. F testresults stating that the motivating factors simultaneously influence the productivity of employees withF observed (7.350) > F table (2.44) and the probability value (0.000) < alpha (0.05). T test results states thatphysiological needs t observed (2.667) > t table (2.01410)and the probability of 0.011 < alpha (0.05) so thatthe partial effect on employee productivity..Keywords: Motivation Factors and Employee Productivity